The Solution of Economic Tasks with the Help of Probability Theory - Yuldashev Sanjarbek Arslon o‘g‘li (Zien Journals, 2023)
The article deals with economic problems, the solution of which occurs using probability theory. The process of solving some economic problems with the help of probability theory is shown. The authors, using the example of an economic problem solved with the help of the formula of total probability, described in detail the course of its solution. An example of an economic problem solved using the Bernoulli formula with a complete description of the problem solution itself is also given. The article noted the importance of economists owning this material, since the correct application of the methods of probability theory helps to correctly predict the possibility of success or failure with maximum accuracy. In this regard, the authors boldly emphasize that economists need knowledge of the theory of probabilities for application in their professional activities, which will help improve the efficiency of the economy
Keywords: probability theory; probability; total probability